2014
DOI: 10.11648/j.ijema.20140205.14
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Natural Radionuclides from Soil to Plants and Grass in the Western North of West Bank Environment- Palestine

Abstract: The transfer factors of radionuclides (226 Ra, 238 U, 232 Th, 40 K and fallout radionuclides 137 Cs) from soil to plant and grass collected from the northwest of West Bank environment-Palestine were measured. For soil to plant, the average transfer factor (TF) values were found to be 0.60, 0.50, 0.31, and 1.70 for 226 Ra, 238 U, 232 Th and 40 K respectively. For soil to grass the TF values were found to be 1.26, 1.12, 1.15 and 1.20 for 226 Ra, 238 U, 232 Th and 40 K respectively. For soil to plant, the average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…we can assume that the average values of the soil to grass transfer factors have been found to be in close agreement with those published by the IAEA (1994) except those for potassium which are higher than the IAEA's values as shown in Table 7. The TF of 228 Ra in our study was found to be close to the result found by Harb (Harb et al, 2014) in Egypt but less than the value finds by Mohannad (Mohannad et al, 2014) in Palestine and very higher than that found by Hasan (Hasan et al, 2010) in Pakistan as shown in Table 7. This variation might be due to different soil's physical and chemical properties, the climate in the area the study has been carried out, and some extra practices at operational processing sites.…”
Section: Activity Concentrations -Soil Samplessupporting
confidence: 71%
“…we can assume that the average values of the soil to grass transfer factors have been found to be in close agreement with those published by the IAEA (1994) except those for potassium which are higher than the IAEA's values as shown in Table 7. The TF of 228 Ra in our study was found to be close to the result found by Harb (Harb et al, 2014) in Egypt but less than the value finds by Mohannad (Mohannad et al, 2014) in Palestine and very higher than that found by Hasan (Hasan et al, 2010) in Pakistan as shown in Table 7. This variation might be due to different soil's physical and chemical properties, the climate in the area the study has been carried out, and some extra practices at operational processing sites.…”
Section: Activity Concentrations -Soil Samplessupporting
confidence: 71%
“…Generally speaking, a TF factor for 137 Cs is found to be less than that of all other radionuclides in all plant species. This indicates that 137 Cs is less efficiently transported from soil to plants than other radionuclides such as: 226 Ra, 238 U, 232 Th and 40 K. It was reported that soil-to-plant TF depends on soil properties such as nutrient standard, exchangeable K content, pH and moisture content [8]. In order to analyze the obtained data concerning the transfer of l37 Cs from the soil to the green parts of plants, it should be noted that all samples reveal the transportation of this isotope.…”
Section: The Transfer Factormentioning
confidence: 99%
“…TF depends only on the environmental conditions; therefore, differences in deposition level between sites can be ignored. In this study the transfer factor was calculated from the concentration activity of the dry plant matter divided by the activity in the top layer of the soil and as following [8]:…”
Section: The Transfer Factormentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies were done on different crops and grass. 5,6 The objective of this work is to study the transfer factor (TF) from soil to grass in Al-Bayda area in North East of Libya to be added to the data base for this part of the world, and to be informed about health safety of the radiation hazard due consumption of animal products. Soil samples were taken from five sites from 15 cm depth, after cleaning the top surface of each site from any organic material or debris.…”
Section: Introductionmentioning
confidence: 99%